A Marked Response to Immunosuppressive Intervention for Abruptly Occurring Cardiac Complications in a Case of Juvenile Systemic Sclerosis Overlapped with Dermatomyositis. (21st February 2017) - Nagamori, Tsunehisa; Yoshida, Yoichiro; Takahashi, Hironori; Oka, Hideharu; Kajihama, Aya; Nakau, Koichi; Sugimoto, Masaya; Minami-Hori, Masako; Azuma, Hiroshi
Abstract : Juvenile-onset systemic sclerosis (jSSc) is a rare condition, having unique characteristic features compared to adult-onset SSc. Although cardiac involvement (CI) is known as a leading cause of mortality overall in SSc, the importance of CI in jSSc has not been emphasized. Here we present a 13-year-old female with jSSc overlapped with dermatomyositis (DM) complicated CI. She developed skin thickness and induration, Raynaud's phenomenon, digital pitting scars in fingertips, and skeletal myositis. Oral prednisolone and pulse methotrexate treatment led to the improvement of skin findings; however two weeks after the initiation she suddenly presented with muscle pain and dyspnea within a few days. Cardiac investigations then showed pericardiac effusion and diastolic dysfunction due to significant biventricular hypertrophy causing heart failure. As pericardiac effusion and exacerbation of skeletal myositis were evident, steroid pulse therapy was initiated. Unexpectedly, not only the myositis but also the CI including diastolic dysfunction was improved. She thereafter followed a favorable clinical course without reactivation of the CI or cardiac fibrosis. As a conclusion, close attention to CI must be paid in jSSc patients, especially when skeletal muscle involvement is evident and immunosuppressive therapy may be effective for CI in jSSc in cases where it occurs abruptly.